Effectiveness of biological control of Trichoderma harzianum on soybean leaf rust disease and the production in West Papua Lowland, Indonesia - EKO AGUS MARTANTO; ADELIN E. TANATI; SAMEN BAAN; HERMAN R. TATA; Agustinus Murdjoko (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Martanto EA, Tanati AE, Baan S, Tata HR, Murdjoko A. 2020. Effectiveness of biological control of Trichoderma harzianum on soybean leaf rust disease and the production in West Papua Lowland, Indonesia. Biodiversitas 21: 1935-1939. This study aims to evaluate the application of Trichoderma harzianum in leaf rust disease on soybean and its production. The study was conducted for three months starting from May to July 2017, at Residential Unit 11th Sidey Subdistrict, Manokwari District, West Papua Province, Indonesia. This study was designed using Factorial Complete Randomized Design consisting of two treatment factors and repeated three times. There was no treatment of pathogen inoculation in the field. The tested varieties had a different response to plant height. Burangrang, Grobogan, Dena-1, Anjasmoro, and Detam-1 varieties were categorized as moderate resistant varieties. The Trichoderma harzianum application should be applied in the whole crops of soybean to control environmentally the leaf rust disease. Seeds weight per plot for Dena-1 variety was higher compared to other varieties. The combination of Detam-1 varieties with Trichoderma treatment 2 times resulted in increased production.